Globicephala melas - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Globicephala melas (Traill 1809) [Delphinus] melas Traill 1809, Nicholson's J. Nat. Philos. Chem. Arts, 22: 81. Type Locality: UK, Scotland, "in Scapay Bay, in Pomona, one of the Orkneys". Vernacular Names: Long-finned Pilot Whale. Synonyms: Globicephala intermedius (Harlan 1827). Subspecies:: Subspecies Globicephala melas subsp. melas Traill 1809 Subspecies Globicephala melas subsp. edwardii Smith 1834 Distribution: North Atlantic and southern Oceans: cold-temperate waters. Kasuya (1975) described the historic distribution in the NW Pacific. Conservation: CITES – Appendix II; IUCN – Lower Risk (lc). Discussion: See Van Bree (1971). Formerly called G. melaena but Article 31b of the third edition of the International Code of Zoological Nomenclature (1985 d ) specifically gave melas as an example of a Greek adjective that does not change its ending when transferred to a genus of another gender (see Schevill, 1990 a , b Rice, 1990). Rice (1998:119) recognized G. m. melas (North Atlantic Longfinned Pilot whale), G. m. edwardii (Southern Longfinned Pilot Whale) and an un-named subfossil subspecies of G. melas that occupied the North Pacific. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 728, DOI: 10.5281/zenodo.7316519